'n Riglyn vir die benutting van metafore in die maatskaplikewerk-hantering van seksueel gemolesteerde kinders - Oelofse, M; Weyers, ML (Social Work/Maatskaplike Werk, 2002)
Background: Due to the high incidence of child sexual abuse in South Africa and an increasing number of cases being reported to social work institutions, practitioners have come under pressure to deliver more effective therapeutic services to especially the victims of such circumstances. Their interventions has, however, been hampered by two factors. They are the absence of wellgrounded treatment programmes and a lack of therapeutic techniques and aids that would meet local needs. Objectives: To develop a treatment programme that could be used as a guideline for intervention and to determine the usefulness of metaphors as therapeutic tools in the application of this programme. Method: The research encompassed the establishment of a tentative treatment programme and its testing and refinement through multiple case studies. These cases covered more than 107 children that were allocated to the researcher while she was working at the Welcome Child Guidance Clinic between 1992 and 1999. The development and testing of metaphors formed an integral part of this process. The results that were obtained will be covered in two separate papers, one pertaining to the programme itself and the other to the use of metaphors. (Part One) Results re the treatment programme: The programme was found to be an effective instrument in the delivery of therapeutic services. It especially gave structure to a complex process and ensured that all relevant issues would be covered in a systematic albeit unobtrusive way.